The square root of 2 is 1.41
Answer: 0
Step-by-step explanation:
Since m is with x, you don't need to care about y
We would get 2x - 6x + 4x = mx
0x = mx
m is 0
Answer:
<u>f(x) = = (x + √2 i) (x - √2 i) (x - 2 ) (x + 1)</u>
Step-by-step explanation:
The given function is f(x) = x⁴ - x³ -2x -4
factor the polynomial function
f(x) = x⁴ - x³ -2x -4 = (x⁴ - 4) - (x³ + 2x ) ⇒ take (-) as a common from (- x³ -2x)
= (x² + 2 ) (x² - 2) - x (x² + 2) ⇒ take (x² + 2) as a common
= (x² + 2 ) ( x² - x - 2)
= (x + √2 i) (x - √2 i) (x -2 ) ( x+1)
Notes: (x⁴ - 4) = (x² + 2 ) (x² - 2)
(x² + 2)= (x + √2 i) (x - √2 i)
( x² - x - 2) = (x -2 ) ( x+1)
20/5 and -20/-5 are equivalent